Te social portrait of women refused from smoking during pregnancy: a study based on birth register - O. A. Kharkova; A. G. Soloviev; A. A. Kovalenko; J. O. Odland (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
Te aim of the study was to explore the prevalence of quitting smoking during pregnancy and to determine factors associated with the latter. We used data from Murmansk County Birth registry from 2006 to 2011. Chi-squared tests and logistic regression were applied. We found that one-fourth smoking before pregnancy woman stopped to do it afer pregnancy recognition. Moreover, we made a social portrait of women who could quit smoking during pregnancy — urban, married women, with higher level of education, and without children (that is primiparous).